(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
The economic crisis which has emerged over recent years has turned out to belong and extremely deep. Furthermore, it has affected the world economy in differentareas. Since the first signs began in 2007, the main indicators of the most powerful world economies have been measuring the effects in the crisis. In many cases, the crisis has led to political, economic and social deterioration of emergingand developed countries. This article analyses the impact of the crisis on the stockmarket through a selection of the main economic indicators that have a strong influenceover market index evolution.This assessment of the markets during the economic crisis is the personal opinion of the author of this article, who has over 38 years experience in the profession.